O habitus migratório de um município mineiro: uma análise a partir de egressos do ensino médio de Governador Valadares - Lima, Ricardo Gomes (2024)
This study adopted Bourdieu's theory of habitus, with an emphasis on migration, as a theoretical lens to understand the migratory phenomenon in Governador Valadares, MG. The objective was to verify whether the formative process of participants from private, federal, and state education networks influenced their views on migration in the municipality and to deepen the analysis of the perspectives of young people from Governador Valadares on emigration, characterizing the migratory habitus and the set of capitals for its consolidation. The study was structured into two articles: the first presented a literature review specifically focused on the application of Bourdieu's theory to the analysis of various migration studies. It was evidenced that this approach provides a valuable analytical perspective for understanding migratory phenomena. Among Bourdieu's concepts explored, habitus and the interconnection between different types of capital were the most frequently employed by researchers. Habitus proved fundamental in understanding migratory dynamics, influencing the trajectories and experiences of migrants. Additionally, the analysis of the interconnection between various capitals reveals transformations in the trajectory of migrants throughout the migratory process. The second article presented qualitative research on the migratory phenomenon in Governador Valadares through a structured questionnaire applied to former students of the integrated education program at the Federal Institute of Education, Science, and Technology - Governador Valadares campus, regular high school education from the state education network, and private high school education in the municipality. The hypothesis was that the formative process in the different education networks present in the municipality constitutes acquired cultural capital, potentially providing different views on the current context of the municipality and the aspects of the identified migratory habitus. This hypothesis was partially confirmed by the study.